Charlotte Brontë the novels - Edwards, Mike 1942- (Analysing texts, 1999)
Readers are encouraged to participate in the analysis, to have confidence in their own responses, to think out their own interpretations and to explore creatively the unique blend of realism and fantasy underlying the psychological power of the novels."--BOOK JACKET